Masa Depan Tafsir Al-Qur'an di Era Digital: Peluang, Tantangan, dan Reorientasi Hermeneutika - Zainal Abidin; Iqbal Muhajir Rul Koto; Achyar Zein; Rahayu Fuji Astuti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the transformation of Quranic exegesis (tafsir) in the digital era, focusing on opportunities, challenges, and hermeneutical reorientation. The methodology employs a qualitative approach with literature studies and descriptive analysis of various digital platforms providing Quranic interpretation services. The findings indicate that the digital era offers significant opportunities in democratizing access to tafsir, facilitating cross-madhab verse search and interpretation, and developing interactive exegetical methodologies. However, major challenges include the validity and authority of digital tafsir sources, interpretation polarization, and degradation of classical scholarly traditions. Hermeneutical reorientation is necessary through developing digital epistemology that maintains classical hermeneutical principles while being adaptive to technological dynamics. This research contributes to developing a comprehensive digital hermeneutical framework for Quranic exegesis relevant to contemporary needs.